DEVELOPMENT OF A LOW-COST COLORIMETER-LIKE FOR UNDERGRADUATE CLASSES USING MICROCONTROLLER BOARD AND RGB LED - Magro, Angelo [UNESP]; Silva, Martin [UNESP]; Sousa, Guilherme [UNESP]; Cardoso, Fábio [UNESP]; Guimarães, Gabriel [UNESP]; Muniz, Sérgio; Sarnighausen, Valéria [UNESP]; Fontes, Marcos [UNESP]; Simões, Rafael [UNESP] (Universidad Nacional Autonoma de Mexico, 2020)
Teaching and learning strategies that use innovating technologies, such as the development of software or an understanding of the theoretical concepts of analytical equipment, can be essential tools for the construction of knowledge. In this way, this work describes the construction of an innovative and lowcost colorimeter using a RGB LED and a microcontroller board as a guide for teachers of undergraduate classes to prepare pedagogical activities using the proposed device as a learning object. The device was applied in experiments using methylene blue (MB), methylene orange (MO) and cobalt chloride (CC) aqueous solutions of different concentrations. Each one of these solutions has absorption peaks near the RGB colors. The results demonstrated that this lowcost device was able to identify unambiguous absorption peaks in the expected range of the MB, MO and CC absorption spectrums, allowing us to determine a feasible calibration curve for each tested solution.
Desarrollo de un colorímetro de bajo costo para las clases de pregrado utilizando una placa de microcontrolador y LED RGB
Keywords: Aprendizaje práctico; colorimetry; colorimetría; Hands-on learning; microcontrolador; microcontroller; STEM